1971
DOI: 10.1002/star.19710230104
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of the Starch/Water System Part I. Measurement of Heat of Gelatinisation by Differential Scanning Calorimetry

Abstract: The application of Differential Scanning Calorimetry to the gelatinisation of concentrated starch/water suspensions produced a well‐defined endotherm under suitable conditions. Measurement of the peak area enabled the heat of gelatinisation to be calculated. The method has been applied to the following aspects of gelatinisation: — 1 Intercomparison of different starches, 2) Effect of granule size, 3 Application to wheat flour, 4 Effect of starch damage, 5 Staling of starch gels, 6 Amylose and amylopectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
79
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(91 citation statements)
references
References 12 publications
8
79
0
Order By: Relevance
“…Lower enthalpy shows the less stability of the crystals (Chiotelli and Meste 2002). The thermal properties of starches were influenced by granule shape, amylopectin chain length and crystalline regions (Noda et al 1996;Stevens and Elton 1971;Singh and Kaur 2004). Differences of R values between samples suggest that the presence of transforms in crystalline regions of the starch granules.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Lower enthalpy shows the less stability of the crystals (Chiotelli and Meste 2002). The thermal properties of starches were influenced by granule shape, amylopectin chain length and crystalline regions (Noda et al 1996;Stevens and Elton 1971;Singh and Kaur 2004). Differences of R values between samples suggest that the presence of transforms in crystalline regions of the starch granules.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Both gelatinization and swelling are properties partially controlled by the molecular structure of amylopectin (unit chain length, extent of branching, molecular weight, and polydispersity), amylose to amylopectin ratio and granule architecture (crystalline to amorphous ratio) (Tester & Morrison, 1990). Differential scanning calorimetry (DSC) is known as an extremely valuable tool to characterize and control the gelatinization phenomenon of starch (Stevens & Elton, 1971) because it provides a quantitative measurement of the enthalpy, ΔH, which means the energy required to take place the gelatinization process, and a determination of temperature range where gelatinization occurs as well. DSC curves recorded for all starches showed an endotherm peak associated to gelatinization phenomenon and thus, based on it, the temperatures involved in this process and gelatinization enthalpy were determined.…”
Section: Gelatinizationmentioning
confidence: 99%
“…It is well known that mutant maize genes have large effects on starch development and properties (Creech 1965, Stevens and Elton 1971, Yeh et al 1981, Inouchi et al 1984, Brockett et al 1988, Wang et al 1992, Campbell et al 1994. Sanders et al (1990) showed that genetic background, other than major mutant genes, influenced thermal starch properties when comparing four corn (three sweet, one dent) inbred lines.…”
mentioning
confidence: 99%